1995
DOI: 10.1038/374091a0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of thyroid-hormone receptor with a conserved transcriptional mediator

Abstract: The thyroid-hormone receptors are hormone-dependent transcription factors that control expression of many target genes. This regulation is presumably a consequence of hormone-dependent contacts between the receptors and the basal transcription machinery. We used the yeast two-hybrid system to identify a candidate human transcriptional mediator that interacts with both the thyroid-hormone receptor and the retinoid-X receptor in a ligand-dependent fashion. This protein, Trip1 (for thyroid-hormone-receptor intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
223
0
3

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 409 publications
(234 citation statements)
references
References 16 publications
8
223
0
3
Order By: Relevance
“…The results of genetic and transfection experiments have also indicated that some of these ATPases participate in transcriptional regulation. It has been suggested that yeast SUG1 acts as a mediator for a transcriptional activator in vivo (Swaffield et al 1992), and Trip1 (human SUG1) and mouse SUG1 were demonstrated to interact with various hormone receptors (Lee et al 1995;vom Baur et al 1996). Recently, mouse SUG1 was demonstrated to have a DNA helicase activity .…”
Section: Are Proteasomal Atpases Candidates For Transcriptional Regulmentioning
confidence: 99%
“…The results of genetic and transfection experiments have also indicated that some of these ATPases participate in transcriptional regulation. It has been suggested that yeast SUG1 acts as a mediator for a transcriptional activator in vivo (Swaffield et al 1992), and Trip1 (human SUG1) and mouse SUG1 were demonstrated to interact with various hormone receptors (Lee et al 1995;vom Baur et al 1996). Recently, mouse SUG1 was demonstrated to have a DNA helicase activity .…”
Section: Are Proteasomal Atpases Candidates For Transcriptional Regulmentioning
confidence: 99%
“…50 nM of the guanine nucleotide bound form of RhoA fused to GST was incubated with 1.5 lal of in vitro translated PKN in a total volume of 200 Ixl of binding buffer (20 mM Tris/HC1 at pH 7.5, 1 mM EDTA, 0.5 mM DTr, 5 mM MgC12 and 1 I.tg/ml leupeptin) for 60 rain at 4°C. Then 40 ~tl of glutathione-Sepharose beads preincubated in binding buffer containing 10 mglml E. coli extracts to block non-specific binding [10], was added and rotated for 30 min at 4°C. Unbound proteins were removed by four washes with binding buffer containing 0.2% Nonidet P-40 and 50 mM NaC1, and by two washes with binding buffer.…”
Section: 3 Preparation Of Recombinant Proteands and In Vitro Bindingmentioning
confidence: 99%
“…These activities are mostly involved in the regulation of transcription in some way. For example, SUG1 (also called Trip1) can interact with nuclear hormone receptors and the basal transcriptional machinery (vom Baur et al, 1995;Lee et al, 1995), thus serving as a transcriptional mediator. It also possesses DNA helicase activity (Fraser et al, 1997) and binds directly to TBP .…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that the proteasomal regulatory component mouse SUG1 (mSUG1) which is of similar molecular weight will bind to the immediate early gene product c-Fos (Wang et al, 1996), TBP and nuclear receptors such as those for thyroid hormone (Lee et al, 1995). With this in mind, a possible interaction of Ad E1A with hSUG1 was investigated.…”
Section: Ad E1a Binds To Sug1mentioning
confidence: 99%
See 1 more Smart Citation